Government Stock Purchase Undermines Price Informativeness: Evidence from China’s “National Team” - Dang, Tri Vi; Li, Wei; Wang, Yongqin (Journal of Financial and Quantitative Analysis, 2024)
Abstract We use the 2015 Chinese stock market crash to study the effects of government stock purchases. The Chinese government purchased stocks to stabilize the markets through state-owned financial institutions known as the “National Team.” We find that the intervention led to reduced volatility and price informativeness. These impacts are driven by the disclosure of government portfolios. Consistent with investors having a stronger incentive to acquire government intervention information instead of fundamental news, we find reduced information production and information asymmetry following intervention disclosure. The article suggests that government stock purchases involve a trade-off between stability and informational efficiency.